Minimal Gastrointestinal Disorders in Infants: When It Is Too Early to Treat - Evgeniya G. Makarova; Tatiana V. Klepikova; Sergey E. Ukraintsev (Вопросы современной педиатрии)
Functional and anatomical development coupled with functional immaturity of gastrointestinal tract present major risk factor for functional gastrointestinal disorders development in infants. The article discusses some aspects of aetiology, prevention and early treatments of gastrointestinal discomfort in infants.